Bagaimana Self-Regulated Learning pada Calon Guru Matematika? - Hani Rosyidah; Ferisa Prasetyaning Utami; Rini Setiawati (Universitas Muria Kudus, 2024)
Self-regulated learning can be explained as a state of learners actively and organized involved in monitoring and regulating cognition and behavior during the learning process, which affects the achievement of learning goals. Self-regulated learning ability is essential for students to achieve optimal academic performance. The research used was a survey using quantitative methods involving 103 prospective mathematics teachers. Data were collected using the self-regulated learning scale developed by Purdie et al. which identified ten dimensions of self-regulated learning, namely self-evaluation, organizing and transforming, goal setting and planning, seeking information, keeping records and monitoring, environmental structuring, self-consequences, rehearsing and memorizing, seeking social assistance and reviewing records. The results of this study indicate that prospective mathematics teachers have moderate self-regulated learning. This research is used as a basis for efforts to improve self-regulated learning in the scope of Guidance and Counseling.